Stratifying infants with cystic fibrosis for disease severity using intestinal organoid swelling as a biomarker of CFTR function. Issue 3 (17th September 2018) - de Winter-de Groot, Karin M.; Janssens, Hettie M.; van Uum, Rick T.; Dekkers, Johanna F.; Berkers, Gitte; Vonk, Annelotte; Kruisselbrink, Evelien; Oppelaar, Hugo; Vries, Robert; Clevers, Hans; Houwen, Roderick H.J.; Escher, Johanna C.; et al.
Forskolin-induced swelling (FIS) of intestinal organoids from individuals with cystic fibrosis (CF) measures function of the cystic fibrosis transmembrane conductance regulator (CFTR), the protein mutated in CF. We investigated whether FIS corresponds with clinical outcome parameters and biomarkers of CFTR function in 34 infants diagnosed with CF. Relationships with FIS were studied for indicators of pulmonary and gastrointestinal disease. Children with low FIS had higher levels of immunoreactive trypsinogen (p=0.030) and pancreatitis-associated protein (p=0.039), more often had pancreatic insufficiency (p<0.001), had more abnormalities on chest computed tomography (p=0.049), and had lower z-scores for maximal expiratory flow at functional residual capacity (p=0.033) when compared to children with high FIS values. FIS significantly correlated with sweat chloride concentration (SCC) and intestinal current measurement (ICM) (r= −0.82 and r=0.70, respectively; both p<0.001). Individual assessment of SCC, ICM and FIS suggested that FIS can help to classify individual disease severity. Thus, stratification by FIS identified subgroups that differed in pulmonary and gastrointestinal outcome parameters. FIS of intestinal organoids correlated well with established CFTR-dependent biomarkers such as SCC and ICM, and performed adequately at group and individual level in this proof-of-concept study. Laboratory-grown mini-guts inform on individual disease characteristics of infants with cystic fibrosis http://ow.ly/J19W30ldzTH